Behaviour of Thermal Power Plant Boiler Support Steel Structure under Seismic Excitations - Arun Kumar, R.; Umarani, C. (Asian Journal of Engineering and Applied Technology, 2019)
Static and dynamic analysis of a thermal power plant boiler support steel structure is carried out to study its behaviour and responses. Non-Linear Time History Analysis (NLTHA) method is adopted to study the behaviour and response of the structure in addition with Equivalent Static Analysis (ESA) and Response Spectrum Analysis (RSA) methods using SAP2000 software application. Though NLTHA method is not used extensively in Indian boiler support structure design practices, in the present study, an attempt is made to study about the realistic behaviour and performance of boiler support steel structure using NLTHA. Three different ground motions are used for analysing the boiler support steel structure with compatible scale factors and during the analysis, behaviour of the structure under different seismic excitations are usually compared in terms of [5] load-deflection, moment-rotation, moment-curvature and stress-stain relationships. Hence it is found that NLTHA method provides more accurate and dynamic results compared to the ESA and RSA methods. Various seismic demand parameters like mode shapes, displacements, drifts, base shear forces, floor accelerations and floor response spectra curves are presented in the results to understand the behaviour and response of the boiler support steel structures during the seismic excitations.